Medical treatments for idiopathic pulmonary fibrosis: a systematic review and network meta-analysis. Issue 12 (10th February 2022) - Pitre, Tyler; Mah, Jasmine; Helmeczi, Wryan; Khalid, Muhammad Faran; Cui, Sonya; Zhang, Melanie; Husnudinov, Renata; Su, Johnny; Banfield, Laura; Guy, Brent; Coyne, Jade; Scallan, Ciaran; et al.
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a respiratory disorder with a poor prognosis. Our objective is to assess the comparative effectiveness of 22 approved or studied IPF drug treatments. Methods: We searched MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and clinicaltrials.gov from inception to 2 April 2021. We included randomised controlled trials (RCTs) for adult patients with IPF receiving one or more of 22 drug treatments. Pairs of reviewers independently identified randomised trials that compared one or more of the target medical treatments in patients with IPF. We assessed the certainty of evidence using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach for network meta-analysis. We calculated pooled relative risk (RR) ratios and presented direct or network estimates with 95% credibility intervals (95% CI), within the GRADE framework. Results: We identified 48 (10 326 patients) eligible studies for analysis. Nintedanib [RR 0.69 (0.44 to 1.1), pirfenidone [RR 0.63 (0.37 to 1.09); direct estimate), and sildenafil [RR (0.44 (0.16 to 1.09)] probably reduce mortality (all moderate certainty). Nintedanib (2.92% (1.51 to 4.14)), nintedanib+sildenafil (157 mL (–88.35 to 411.12)), pirfenidone (2.47% (–0.1 to 5)), pamrevlumab (4.3% (0.5 to 8.1)) and pentraxin (2.74% (1 to 4.83)) probably reduce decline of overall forced vital capacity (all moderate certainty). Only sildenafil probably reduces acute exacerbation and hospitalisations (moderate certainty). Corticosteroids+azathioprine+N-acetylcysteine increased risk of serious adverse events versus placebo (high certainty). Conclusion and relevance: Future guidelines should consider sildenafil for IPF and further research needs to be done on promising IPF treatments such as pamrevlumab and pentraxin as phase 3 trials are completed.